Supplementation of molasses and branched-chain amino acid to increase in vitro digestibility of ammoniated corn cob in ruminants feed - Wisri Puastuti; Dwi Yulistiani; Eko Handiwirawan (Indonesian Center for Animal Research and Development (ICARD), 2017)
Corn cob contains high fiber and lignin which causes low nutritive value. The objective of the study was to improve the digestibility of ammoniated corn cob (CC) by supplementation of molasses and branched-chain amino acid (BCAA: valine, leucine and isoleucine). CC was processed by addition 3% urea. The first stage of in vitro test was done with 4 levels of molases 0, 5, 10 and 15% of dry matter (DM) of CC. The experiment was carried out using complete randomized design with 4 treatments and 4 replications. The second stage was also in vitro study of supplementation of two levels each for valine = V, leucine = L and isoleucine = I namely 0.1 and 0.2% of DM of ammoniated CC. There were 8 treatments combination of the BCAA as follow: A = V0.1 L0.1 I0.1; E = V0.2 L0.1 I0.1; B = V0.1 L0.1 I0.2; F = V0.2 L0.1 I0.2; C = V0.1 L0.2 I0.1; G = V0.2 L0.2 I0.1; D = V0.1 L0.2 I0.2; H = V0.2 L0.2 I0.2 and 1 control (V0.0 L0.0 I0.0). The experiments were done using completely randomized design with 9 treatments and 3 replications. The results showed that treated CC with urea was able to increase protein content by 78% (increased from 3.34% to 5.95%) while neutral detergent fiber (NDF) decreased by 15.4%, acid detergent fiber (ADF) by 7.9% and lignin 16.7%. Addition of molasses in ammoniated CC increased DM digestibility (P <0.05) by 7.5% (41.9 vs 43.51-46.26%) and NDF by 17.7% (38.41 vs 43.76 – 46.31%). Supplementation of BCAA resulted in the highest DM, OM and NDF digestibility (P <0.05) in the treatment of A, C, D and G. Compare to treament I, the digestibility of DM, OM and NDF in G treatment increased by 31.4%, 27.5% and 36.5%, respectively and produced the highest total population of rumen bacterial of 12.4 x 109 colonies /ml. It can be concluded that the digestibility of ammoniated CC increased by the supplementation of 5% molases and BCAA combination consisted of 0.2% valine, 0.2% leucine and 0.1% isoleucine. Kata kunci: Tongkol jagung, amoniasi, molases, asam amino bercabang.